MEASURING QUALITY OF WIRELESS LOCAL AREA NETWORK USING QUALITY OF SERVICE FRAMEWROK - Aliy Hafiz; Dodi Afriansyah; Fathurrahman Kurniawan Ikhsan; Bambang Suprapto; Ifo Wahyu Pratama (IJISCS (International Journal of Information System and Computer Science), 2019)
The internet has a very important role in education. Many activities are done through internet. AMIK DCC Bandar Lampung is an educational institution that uses the internet as one of the supporting facilities and infrastructures to manage and organize the data and information used by the student to find references about the lecture. There are three buildings on the main campus building A building B and C buildings, where each building using WLAN to deploy internet access. There are some complaints submitted by students related wireless network encourage researchers to study the quality of service WLAN. Thus the researchers wanted to analyze the Quality of Service WLAN networks in building A, building B, and C, in each floor. The method used in this research is Quality of Services (QoS). Where an analysis wireless network by four parameters. There are namely delay, packet lost, bandwidth, and throughput. The results of the measurement and monitoring of Quality of Service WLAN at AMIK DCC Bandar Lampung in building A, building B, C on each floor of the building can be classified in the category of good which value index is 3, and the factors that occurred in the signal range cannot cover every room in every building and have not good bandwidth management.